Melanoma maligno associado a nevo melanocítico - Gomes, J (2013)
Objectives: To determine clinical and histopathological differences between melanoma associated with nevus (MAN) and de novo melanoma (MN). Methods: Retrospective study of all cases of cutaneous melanoma diagnosed between 2001 and 2009 in Centro de Dermatologia Médico-Cirúrgica de Lisboa. Results: Of the 397 melanomas included, 52.6% were of feminine sex and 47.4% of the masculine. Of these melanomas only 9.3% were histologically associated with nevus, with discrete predominance of cases in the feminine sex (54%, p=0,033). In the group of the MAN the average of ages was slightly inferior (56,5 vs 59,3 years, p=0,577). The trunk was the preferential localization of all the melanomas (42.1%, p=0,005). Histologically the superficial spreading subtype was more frequently associated with MAN. The MAN were thinner than the MN (1,42 versus 2,13 mm, p=0,030), specially in the feminine sex (0,99mm, p=0,031). The Breslow tumor thickness and the presence of ulceration had a significant statistical correlation with the metastatic spread and the mortality by melanoma. Conclusions: The majority of the melanomas seem to arise de novo. In our study, factors that were significantly associated with MAN include feminine sex, trunk location, younger age, inferior Breslow thickness and superficial spreading subtype.